A STUDY OF MAJOR PROBLEM IN INDONESIAN ANIMATION VOCATIONAL HIGH SCHOOL - Rochman, Mochamad Faizal; Ming, Zhong Xing; Masduki, Anang (PEOPLE: International Journal of Social Sciences, 2020)
When the government opens an animation competency on vocational high school (VHS), it is expected to be able to meet the animation industry needs. However, the facts show that graduated students from VHS contribute to the highest unemployment amongst other school educations. This paper tries to identify the existing problems faced by the graduates of the animation program before they enter the real world and analyze the underlying reasons. We conducted an in-depth interview with several teachers, principals, and students, also study literature reviews to collects data. The major problem shows that first, there are still many teachers who lack competencies to teach animation. Second, parents want their children to go to higher-level education in order to get a better life. Thirdly, each VHS that has an animation program must have specialization so that students can master a specific animation area. Fourth, students need to emphasize entrepreneurial skills through social media. This study also presented some recommendations for government as the central role of the education system, and for animation VHS as an education institution in regarding the major problem faced by graduated students.